Comparison of the Microtensile Bond Strength Of Four Different Bulk-Fill Resin Composites Of Class I Cavities With Dentin - Serra Kutlu; İhsan Hubbezoğlu (Cumhuriyet University, 2019)
Objectives: The aim of our study is to compare the microtensile bond strengths of four different bulk-fill composites and a microhybrid composite to the dentin. Materials and methods: 4 bulk-fill composites and a microhybrid composite were tested. Class I occlusal cavities were prepared on 25 freshly drawn intact human molar teeth, randomly divided into five groups [G-aenial posterior(Control group), Estelite Bulk Fill flow, GrandioSO x-tra, Beautiful Bulk Restorative, Fill-Up] and the cavities were restorated with five composite systems by using their own adhesive systems. Completed restoration teeth bukkolingual and mesiodistal sections were taken, three samples were obtained from each tooth(n:15). Microtensile bond strength values of groups were measured by universal test machine. Microscopic changes were examined by SEM. The data were evaluated by one-way ANOVA and Tukey tests. Results: While the control group showed the highest microtensile bond strength, Fill-Up group showed the lowest. The control group was statistically significant when compared to the four different bulk-fill groups used in the study(p<0.05). Although the GrandioSO x-tra group showed the highest bonding strength among the bulk-fill composites, the differences between the Beautifil Bulk Restorative and Estelite Bulk Fill flow were statistically insignificant(p>0.05). Fill-Up was found to be statistically significant when compared to the other bulk-fill groups(p<0.05). In SEM analyzes a regular gap is seen along the hybrid layer only in Estelite Bulk Fill flow. Conclusions: No bulk-fill composite group could reach the value of the bond strength of microhybrid composite. Although the Fill-Up group was used with the etch and rinse adhesive system among the bulk-fill composites, it showed the lowest bond strength.results: While the control group showed the highest microtensile bond strength, Fill-Up group showed the lowest. The control group was statistically significant when compared to the four different bulk-fill groups used in the study(p<0.05). Although the GrandioSO x-tra group showed the highest bonding strength among the bulk-fill composites, the differences between the Beautifil Bulk Restorative and Estelite Bulk Fill flow were statistically insignificant(p>0.05). Fill-Up was found to be statistically significant when compared to the other bulk-fill groups(p<0.05). In SEM analyzes a regular gap is seen along the hybrid layer only in Estelite Bulk Fill flow.Conclusions: No bulk-fill composite group could reach the value of the bond strength of microhybrid composite. Although the Fill-Up group was used with the etch and rinse adhesive system among the bulk-fill composites, it showed the lowest bond strength.Results: While the control group showed the highest microtensile bond strength, Fill-Up group showed the lowest. The control group was statistically significant when compared to the four different bulk-fill groups used in the study(p<0.05). Although the GrandioSO x-tra group showed the highest bonding strength among the bulk-fill composites, the differences between the Beautifil Bulk Restorative and Estelite Bulk Fill flow were statistically insignificant(p>0.05). Fill-Up was found to be statistically significant when compared to the other bulk-fill groups(p<0.05). In SEM analyzes a regular gap is seen along the hybrid layer only in Estelite Bulk Fill flow.Conclusions: No bulk-fill composite group could reach the value of the bond strength of microhybrid composite. Although the Fill-Up group was used with the etch and rinse adhesive system among the bulk-fill composites, it showed the lowest bond strength.